Effect of Sublethal Prenatal Endotoxaemia on Murine Placental Transport Systems and Lipid Homeostasis - Reginatto, Mila W.; Fontes, Klaus Novaes; Monteiro, Victoria R. S.; Silva, Natalia L.; Andrade, Cherley Borba Vieira; Gomes, Hanailly Ribeiro; Imperio, Guinever E.; Bloise, Flavia Fonseca; Kluck, George Eduardo Gabriel; Atella, Georgia Correa; Matthews, Stephen G.; Bloise, Enrrico; et al. (Frontiers in Microbiology, 2021)
Infection alters the expression of transporters that mediate the placental exchange of xenobiotics, lipids and cytokines. We hypothesized that lipopolysaccharide (LPS) modifies the expression of placental transport systems and lipid homeostasis. LPS (150 μg/kg; i.p.) treatments were administered for 4 h or 24 h, animals were euthanized at gestational days (GD) 15.5 or 18.5, and maternal blood, fetuses and placentae were collected. Increased rates of fetal demise were observed at GD15.5 following LPS treatment, whereas at GD18.5, high rates of early labour occurred and were associated with distinct proinflammatory responses. Lipopolysaccharide did not alter ATP-binding cassette (ABC) transporter mRNA expression but decreased fatty acid binding protein associated with plasma membrane (Fabppm) at GD15.5 (LPS-4 h) and increased fatty acid translocase (Fat/Cd36) mRNA at GD18.5 (LPS-4 h). At the protein level, breast cancer-related protein (Bcrp) and ABC sub-family G member 1 (Abcg1) levels were decreased in the placental labyrinth zone (Lz) at GD15.5, whereas P-glycoprotein (P-gp) and Bcrp Lz-immunostaining was decreased at GD18.5. In the placental junctional zone (Jz), P-gp, Bcrp and Abcg1 levels were higher at GD18.5. Specific maternal plasma and placental changes in triacylglycerol, free fatty acid, cholesterol, cholesterol ester and monoacylglycerol levels were detected in a gestational age-dependent manner. In conclusion, LPS-increased risk of fetal death and early labour were associated with altered placental ABC and lipid transporter expression and deranged maternal plasma and placental lipid homeostasis. These changes may potentially modify fetal xenobiotic exposure and placental lipid exchange in cases of bacterial infection.